1999
DOI: 10.1063/1.125022
|View full text |Cite
|
Sign up to set email alerts
|

Photostimulated luminescence in a rare earth-doped fluorobromozirconate glass ceramic

Abstract: Photostimulated luminescence at room temperature was observed in a fluorozirconate glass which was doped with 1% Eu2+ or 1% Ce3+ and 5% Br− ions. Small crystals of BaBr2 (high-pressure phase) form in the glass on cooling. The Eu2+ and Ce3+ luminescence spectra comprised two emission lines each: for Eu2+ one line at 413 nm and a broader band centered at 485 nm, and for Ce3+ one line at 320 nm and a broader band at 425 nm. The luminescence is attributed to the 5d14fn−1→4fn emissions of the rare earth ions. In bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 9 publications
1
32
1
Order By: Relevance
“…Model of an H-type F À 2 centre in BaFBr with two equivalent fluorine nuclei after [61] much shorter (3.18 A) than the Br ---Br --distance, either in plane (4.50 A) or out of plane (3.72 A). Also there are linear [110] or [100] chains of equivalent F --ions, whereas the hole motion within the Br --double layer would need to proceed in a zigzag motion to separate from the F centre. The former pathway resembles more the situation in the alkali halides, where the hole motion is known to proceed along the [110] halogen chain.…”
Section: Generation Of Electron and Hole Trap Centresmentioning
confidence: 99%
See 1 more Smart Citation
“…Model of an H-type F À 2 centre in BaFBr with two equivalent fluorine nuclei after [61] much shorter (3.18 A) than the Br ---Br --distance, either in plane (4.50 A) or out of plane (3.72 A). Also there are linear [110] or [100] chains of equivalent F --ions, whereas the hole motion within the Br --double layer would need to proceed in a zigzag motion to separate from the F centre. The former pathway resembles more the situation in the alkali halides, where the hole motion is known to proceed along the [110] halogen chain.…”
Section: Generation Of Electron and Hole Trap Centresmentioning
confidence: 99%
“…Also there are linear [110] or [100] chains of equivalent F --ions, whereas the hole motion within the Br --double layer would need to proceed in a zigzag motion to separate from the F centre. The former pathway resembles more the situation in the alkali halides, where the hole motion is known to proceed along the [110] halogen chain.…”
Section: Generation Of Electron and Hole Trap Centresmentioning
confidence: 99%
“…Fluoride nano-crystals have been obtained recently in fluorozirconate glasses, a novel application of fluorozirconate glass-ceramic has been proposed as an x-ray storage phosphor [1,2]. Less investigated are fluoride crystallites in oxyfluorides: aluminate [3][4][5] and SiO 2 glasses [6]; new interesting properties of the so-called up-conversion have been reported in [4][5][6].…”
Section: Introductionmentioning
confidence: 98%
“…As in the previous studies, researchers have focused on controlling color and efficiency by manipulating the active ions in the glass. Edgar et al 46 reported a fluorobromozirconate glass doped with Eu 2+ /Ce 3+ . Lakshminarayana et al 47 reported Tm 3+ /Dy 3+ co-doped oxyfluoride germinate glasses for white light emission.…”
Section: Glass Phosphor Plate (Gpp)mentioning
confidence: 99%